Identification of virion polypeptides in hamster cells transformed by herpes simplex virus type 1. - Gupta, P (1977)
Ten polypeptides were detected on the surface of the virion of herpes simplex virus type 1. Of these ten polypeptides, three were detected in hamster cells transformed by herpes simplex type 1.